Design of an Air Quality Monitoring and Control System Using Internet of Things. - Dwire, Jelly Jophian (Kabale University, 2023)
Air pollution is one of the leading global public health risks but its magnitude in many developing countries' though in most cities it is not known. The level of air pollution has increased with times b, lot of f'actors ranging from increase in population, industrialization and urbanization which results in harmful effects on human wellbeing by directly affecting health of population exposed to it. The currently used systems however that are commonly imported in Uganda do not have an automated monitoring mechanism. they are unreliable. expensive. hard to read and their main l(ic11s is on vehicles yet people spend most of their time working indoors in clilTerenl industries hence their health is compromised. In this system, the air quality sensor. Temperature and humidity sensor are used to detect increase or decrease in the different conditions and taking action by indicating to the responsible personal in the industry at that time